FAKTOR – FAKTOR YANG MEMPENGARUHI PROFITABILITAS STUDI KASUS PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BEI - Ilyasa Deva Wirabuana; Hersugondo Hersugondo (Riset Manajemen dan Akuntansi, 2021)
The purpose of this study is to examine the factors that effect the profitability of non-financial companies listed in Indonesia. This study builds on five existing independent variables and is examined empirically for their relationship to profitability. These variables are company size (as measured by total sales), working capital (WC), company efficiency (asset turnover ratio), liquidity (current ratio), and leverage (debt-equity ratio and leverage ratio). Data on 120 companies listed on the Indonesia stock exchange for the 2017-2019 period are taken from the company’s annual reports. To analyze data, we used Ordinary Least Square (OLS) regression with spss version 21. The findings show a strong positive relationship between firm size (total sales), WC, efficiency (asset turnover ratio), and profitability. In addition, the study also shows a negative relationship between debt to equity and WC on profitability. Liquidity (current ratio) and leverage do not have a significant relationship with profitability